Effectiveness of adalimumab in combination with intense pulsed light and radiofrequency therapy (LAight®) for severe hidradenitis suppurativa: A case report - Uwe Kirschner; Berenice Maureen Lang; Kerstin Steinbrink; Sophia Zimmer (Wolters Kluwer Medknow Publications, 2020)
Hidradenitis suppurativa (HS also named as acne inversa) is a chronic skin disease characterized by relapsing formation of abscesses, inflammatory nodules, and fistulas. In moderate-to-severe disease, HS leads to the formation of scarring and thus irreversible tissue destruction. In the past few years, two new treatment options became available: adalimumab, the first biologic therapy approved for HS (Humira®, AbbVie), and a noninvasive, device-based treatment utilizing a combination of intense pulsed light and radiofrequency (LAight® therapy, LENICURA, Germany). Here, we report a case of a Hurley stage III patient where the positive effect of adalimumab could be enhanced by simultaneously applying LAight® therapy. Moreover, long-term symptom control could be achieved under monotherapy with LAight® after adalimumab was terminated.